CINTA MENYEMBUHKAN PENYAKIT HATI Sebuah Analisa Cinta menurut Ibnu Taymiyya dan Implikasinya bagi Dialog Islam-Kristen - Yan O. Kalampung (Potret Pemikiran, 2016)
Abstract. Ibn Taymiyya as one of Syaikul Islam (Islamic Expert) and Mujaddid (Revolutioner) frequently cited by extrimist in Islam. This fact cannot have a good correlation with his long life works that also talks about love. When the writings about love is cited also, the other side of Ibn Taymiyya can be seen as a basis from Islamic-Christian dialogue. This paper is examines the writings of Ibn Taymiyya that talks about love. To seen his concept clearly, i will compare it with the concept of love in Sufism and also seeks the similarity and differences between them to see its influences in Ibn Taymiyya’s thought. I will try to see The concept of love from Ibn Taymiyya as a basis for dialogue, eventhough many other writings from him is also cited to support the extrimist concept.Keywords : Ibn Taymiyya, Love, Sufism, Islam-Christian dialogue. Abstrak. Ibn Taymiyya sebagai salah satu Syaikul Islam (Ahli Islam) dan Mujaddid (Revolusi) sering dikutip oleh extrimist dalam Islam. Fakta ini tidak dapat memiliki korelasi yang baik dengan karya-karya panjang umurnya yang juga berbicara tentang cinta. Ketika tulisan-tulisan tentang cinta dikutip juga, sisi lain Ibnu Taimiyah dapat dilihat sebagai dasar dari dialog Islam-Kristen. Makalah ini membahas tulisan-tulisan Ibnu Taimiyah yang berbicara tentang cinta. Untuk melihat konsepnya dengan jelas, saya akan membandingkannya dengan konsep cinta dalam Sufisme dan juga mencari kesamaan dan perbedaan di antara mereka untuk melihat pengaruhnya dalam pemikiran Ibnu Taimiyya. Saya akan mencoba untuk melihat konsep cinta dari Ibnu Taimiyah sebagai dasar untuk dialog, meskipun banyak tulisan lain darinya juga dikutip untuk mendukung konsep extrimist.Kata kunci: Ibn Taymiyya, Cinta, Sufisme, dialog Islam-Kristen.